Multimedia Interaktif Sebagai Sarana Pembelajaran Dalam Peningkatan Prestasi Siswa Di Sekolah Pada Masa Pandemi - ., Indah Saputri; ., Mirna Annifah Hasibuan; ., Nurkosrina Aisah; ., Septina Ona Sutra; ., Ali Ikhwan (CV. ITTC INDONESIA, 2022)
Learning media is anything that helps humans in order to understand or learn some theory or material that is useful in order to train abilities or skills. In addition, multimedia is a useful tool for selecting individuals based on the material displayed. Interactive multimedia is designed to have interactive characteristics and is easy to use to help people interact with media content. Interactive multimedia can add meaning to the process because it allows users to interact with the material. Interactive multimedia can also increase student interest in the learning process during a pandemic. This study aims to analyze interactive multimedia in improving students during a pandemic.